2016
DOI: 10.1590/1983-21252016v29n108rc
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Sanitary Quality of Desiccated and Stored Azuki Bean Seeds

Abstract: -The objective of this research was to evaluate the effects of using different herbicides as desiccants in pre-harvest and the effects of storage on the physiological and sanitary quality of azuki bean seeds (Vigna angularis Willd). The experiment was arranged in a randomized complete block design in a split plot scheme, with four replications. Four herbicides were tested: paraquat (400 g a.i. ha -1 ), glufosinate ammonium (400 g a.i. ha -1 ), glyphosate (720 g a.i. ha -1 ), flumioxazin (30 g a.i. ha -1 ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(21 reference statements)
1
7
0
3
Order By: Relevance
“…Studies related to pre-harvest desiccation for seed production have been conducted mainly in crops such as rice (He et al, 2015), beans (McNaughton et al, 2015;Tavares et al, 2016), soybean (Kappes et al al., 2012) and wheat (Jaskulski and Jaskulska, 2014). For the soybean crop, several authors report that pre-harvest desiccation allows uniformity of maturation, promoting uniform drying of the pods and seeds, so that it anticipates the harvest without harming the yield and the quality of the seeds, since they do not induce the dehiscence of the pods (Lacerda et al, 2003;Pelúzio et al, 2008;Kappes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies related to pre-harvest desiccation for seed production have been conducted mainly in crops such as rice (He et al, 2015), beans (McNaughton et al, 2015;Tavares et al, 2016), soybean (Kappes et al al., 2012) and wheat (Jaskulski and Jaskulska, 2014). For the soybean crop, several authors report that pre-harvest desiccation allows uniformity of maturation, promoting uniform drying of the pods and seeds, so that it anticipates the harvest without harming the yield and the quality of the seeds, since they do not induce the dehiscence of the pods (Lacerda et al, 2003;Pelúzio et al, 2008;Kappes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These herbicides did not affect the physiological potential of the seeds after six months of storage, and some variables showed better results than those of the control. Tavares et al (2016) found that paraquat and flumioxazin had no effect on the physiological quality of azuki bean seeds after six months of storage. However, Santos et al (2005) reported that the use of carfentrazone-ethyl as desiccant at preharvest of common bean seeds compromises the physiological potential of stored seeds.…”
Section: Methodsmentioning
confidence: 91%
“…Despite these negative results, the treatment with saflufenacil presented higher EM and ESI than the control (Table 4). Tavares et al (2016) evaluated the effect of different herbicides applied at pre-harvest on seed quality of adzuki bean (Vigna angularis) and found negative effects of glyphosate and glufosinateammonium on seed germination and vigor after six months of storage. These herbicides may have been translocated to seeds still in formation, since they were sprayed directly on the pods, which are located above the leaves, negatively affecting their quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Durante a fase de maturação das sementes, condições ambientais desfavoráveis ao período de colheita podem acarretar no ataque de microrganismos e de pragas vetores de patógenos (Juhász et al, 2013). Sementes que atingiram sua maturidade fisiológica e que permanecem no campo durante algum tempo ao sofrerem mudanças climáticas, especialmente na temperatura e umidade estão sujeitos a sofrer o ataque de patógenos, e consequentemente a ocorrência de efeitos deletério na qualidade fisiológica e sanitária (Tavares et al, 2016).…”
Section: Fatores Que Afetam a Qualidade Sanitária E Favorecem Ao Ataqunclassified